Ultraflexible Vertical Corbino Organic Electrochemical Transistors for Epidermal Signal Monitoring - Lee, Inho; Kim, Ji Hwan; Kim, Youngseok; Shin, Dongjoon; Lee, Hyeongbeom; Won, Jonghyun; Kang, Keehoon; Choi, Jun Gyu; Yoon, Myung Han; Park, Sungjun (Advanced Materials, 2025)
Skin-conformal organic electrochemical transistors (OECTs) have attracted significant attention for real-time physiological signal monitoring and are vital for health diagnostics and treatments. However, mechanical harmonization amid the inherent dynamic nature of the skin surface and the acquisition of intrinsic physiological signals are significant challenges that hinder the integration of the ultimate skin interface. Thus, this study proposes a novel 4-terminal (4-T) vertical Corbino OECT, exhibiting high transconductance (>400 mS) and offering remarkable resilience and operational stability at an extremely low voltage of 10 mV (1.9% of minimal current change after 104 biasing cycles and endurance up to 103 cycles of repetitive deformation with a 5 µm bending radius). Consequently, ultralow-power, motion-resistant epidermal electrocardiogram, electromyogram, and electrooculogram sensors are developed with an exceptional signal-to-noise ratio of 40.1 dB. The results of this study present a significant stride in non-invasive, skin-interfaced health-monitoring technologies and herald a new era in integrative health technologies.
Keywords: Mechanical; Mixed ionic-electronic conductors; Organic electrochemical transistors; Organic mixed ionic–electronic conductor; Organics; Physiological signals; Real- time; Signal monitoring; Ultraflexible device; Vertical devices; Electrocardiography; Electrochemical Techniques; Electromyography; Epidermis; Humans; Monitoring, Physiologic; Signal-To-Noise Ratio; Transistors, Electronic; organic electrochemical transistor; organic mixed ionic–electronic conductor; ultraflexible device; vertical device